2005
DOI: 10.1001/archfaci.7.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Wound Response and Soft Tissue Ingrowth in Synthetic and Allogeneic Implants With Platelet Concentrate

Abstract: To evaluate the modulation of wound healing and soft tissue ingrowth in synthetic and allogeneic implants with platelet gel. Attempts to influence wound healing with exogenous growth factors are highly dependent on the timing and dosing of treatment. Platelet gel made fromautologousplateletconcentrate(PC)andactivatedwith calcium thrombin is increasingly used to enhance healing of surgical and chronic wounds, based on the assumption that proteins found in the blood can promote healing.Methods: Adult New Zealand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 16 publications
(13 reference statements)
0
43
0
1
Order By: Relevance
“…Autologous platelet growth factors have been used by Zieren et al [39], who showed enhanced ingrowth and increased cell proliferation with a higher number of fibroblasts/collagen fibers in abdominal hernia repair, suggesting a role of platelet growth factors in the healing process. Sclafani et al [40] showed an accelerated maturation of wounds in an experimental setting when PLG was used. On the basis of these findings, we have initiated a research program to confirm whether the application of PLG is useful for hernia repair in a clinical setting.…”
Section: Synthetic and Allogeneic Implantsmentioning
confidence: 99%
“…Autologous platelet growth factors have been used by Zieren et al [39], who showed enhanced ingrowth and increased cell proliferation with a higher number of fibroblasts/collagen fibers in abdominal hernia repair, suggesting a role of platelet growth factors in the healing process. Sclafani et al [40] showed an accelerated maturation of wounds in an experimental setting when PLG was used. On the basis of these findings, we have initiated a research program to confirm whether the application of PLG is useful for hernia repair in a clinical setting.…”
Section: Synthetic and Allogeneic Implantsmentioning
confidence: 99%
“…However, we also noted rapid loss of clinical volume when ADG was injected subdermally, 3 and a similar lymphocytic response was noted when sheet ADG was implanted into rabbits. 7 Since minimal lymphocytic response was noted in the human biopsy specimens taken over the first year after implantation, this likely represents an immune response to a xenograft. So what have we learned in the past decade?…”
Section: Methodsmentioning
confidence: 98%
“…In a study examining the effects of PRP, my colleagues and I noted an early increase in endothelial cells and fibroblasts in a wound, which did not persist after 7 days. 6 This early effect on fibroblasts and endothelial cells, however, spurred our interest in harnessing the body's natural mechanisms for wound repair and collagen production for use in softtissue augmentation.…”
Section: Commentmentioning
confidence: 99%